Docentes con función directiva en Liceos Bolivarianos como promotores de aprendizaje organizacional: necesidades de formación - Contreras Chacón, Azael Eduardo (2012)
Educators with leadership roles as promoters of organizational learning in Bolivarian secondary schools: Training needs This article presents partial results of research aimed at detecting the training needs of educators in leadership roles. This explorative and descriptive study analyzed relevant actions and difficulties or obstacles of twenty-four school leaders in their role as organizational learning promoters in two Bolivarian secondary schools in San Cristóbal (Táchira State). The data was collected through a questionnaire administration, semi-structured interviews and observations. Among our findings is the progressive awareness of the school leaders concerning the growth of responsibility as organizational learning promoters for a new school model. Nevertheless, in the taking of this role they face problems, obstacles, resistance and tremendous training needs in many areas, especially when dealing with interpersonal relationships.